An effective in vivo mitochondria-targeting nanocarrier combined with a π-extended porphyrin-type photosensitizer. Issue 20 (9th September 2021) - Satrialdi,; Takano, Yuta; Hirata, Eri; Ushijima, Natsumi; Harashima, Hideyoshi; Yamada, Yuma
Abstract : Novel mitochondria-targeted photodynamic therapy potentiates antitumor activity against both human and murine tumors xenografted in a mouse model. Abstract : A photochemical reaction mediated by light-activated molecules (photosensitizers) in photodynamic therapy (PDT) causes molecular oxygen to be converted into highly reactive oxygen species (ROS) that are beneficial for cancer therapy. As the active oxygen consumer and the primary regulator of apoptosis, mitochondria are known as an important target for optimizing PDT outcomes. However, most of the clinically used photosensitizers exhibited a poor tumor accumulation profile as well as lack of mitochondria targeting ability. Therefore, by applying a nanocarrier platform, mitochondria-specific delivery of photosensitizers can be materialized. The present research develops an effective mitochondria-targeting liposome-based nanocarrier system (MITO-Porter) encapsulating a π-extended porphyrin-type photosensitizer (rTPA), which results in a significant in vivo antitumor activity. A single PDT treatment of the rTPA–MITO-Porter resulted in a dramatic tumor inhibition against both human and murine tumors that had been xenografted in a mouse model. Furthermore, depolarization of the mitochondrial membrane was observed, implying the damage of the mitochondrial membrane due to the photochemical reaction that occurred specifically in the mitochondria of tumor cells. The findings presented herein serve to verify the significance of the mitochondria-targeted nanocarrier system for advancing the in vivo PDT effectivity in cancer therapy regardless of tumor type.